Epoxy/Silicone Blend Loaded with N-Doped CNT Composites: Study on the Optoelectronic Properties - Younes Ziat; Hamza Belkhanchi; Maryama Hammi; Ousama Ifguis (International Journal of Photoenergy)
Thin films of epoxy/silicone loaded with N-CNT were prepared by a method of sol-gel and deposited on ITO glass substrates at room temperature. The properties of the loaded monolayer samples (0.00, 0.07, 0.1, and 0.2 wt% N-CNTs) were analyzed by UV-visible spectroscopy. The transmittance for the unloaded thin films is 88%, and an average transmittance for the loaded thin film is about 42 to 67% in the visible range. The optical properties were studied from UV-visible spectroscopy to examine the transmission spectrum, optical gap, Tauc verified optical gap, and Urbach energy, based on the envelope method proposed by Swanepoel (1983). The results indicate that the adjusted optical gap of the film has a direct optical transition with an optical gap of 3.61 eV for unloaded thin films and 3.55 to 3.19 eV for loaded thin films depending on the loading rate. The optical gap is appropriately adapted to the direct transition model proposed by Tauc et al. (1966); its value was 3.6 eV for unloaded thin films and from 3.38 to 3.1 eV for loaded thin films; then, we determined the Urbach energy which is inversely variable with the optical gap, where Urbach’s energy is 0.19 eV for the unloaded thin films and varies from 0.43 to 1.33 eV for the loaded thin films with increasing rate of N-CNTs. Finally, nanocomposite epoxy/silicone N-CNT films can be developed as electrically conductive materials with specific optical characteristics, giving the possibility to be used in electrooptical applications.